EKPLOITASI TUBUH AKTIVIS PEREMPUAN DALAM PELAKSANAAN PROGRAM KERJA PENGURUS CABANG PERGERAKAN MAHASISWA ISLAM INDONESIA KABUPATEN MALANG - ., Ahmad Zainuri (Program Studi Hukum Keluarga Islam Fakultas Syariah dan Hukum, 2019)
In implementing the works program of the Branch Management of Indonesian Islamic Students Movement of Malang Regency, for the sake of a good and interesting event, the owners of power use female activists to become workers. Women activists must carry out tasks that are not in accordance with their job descriptions, get coercion from fellow activists to carry out tasks that they themselves have not yet experienced and only try first, and the most striking is when female activists are not happy if there is a women's development program. The practice of exploitation of these women activists, seen in this article, uses Michel Foucault's body discipline theory. The body's discipline works as a normalization of behavior designed by utilizing the productive and reproductive abilities of the human body. The practice of power through disciplining the body, creates a situation where the individual body can internalize submission and make it look like a normal state. This practice is what Foucault calls the normalization of power over the individual body. Individuals will never feel that they are being used and subjugated because they already consider it to be within reasonable limits. It can also be said that this is a veiled exploitation.